Long non‐coding RNA SCARNA2 induces cutaneous squamous cell carcinoma progression via modulating miR‐342‐3p expression. (8th November 2020) - Zhang, Zhongzhao; Jia, Min; Wen, Changhui; He, Aijuan; Ma, Zunfeng
Abstract: Background: Long non‐coding RNAs (lncRNAs) play important roles in the progression of tumors. However, the function and expression of SCARNA2 in cutaneous squamous cell carcinoma (cSCC) is still unreported. Methods: A quantitative polymerase chain reaction was applied to study the expression of SCARNA2 and miR‐342‐3p. Cell counting kit‐8, flow cytometry and transwell assays were performed to study cell growth, cycle and cell invasion. Results: We found that SCARNA2 expression is up‐regulated in cSCC cell lines and SCARNA2 expression is higher in cSCC tissues than in adjacent non‐tumor specimens. Ectopic expression of SCARNA2 promoted cell growth, cell cycle and invasion in SCC13 cells. In addition, the data indicate that miR‐342‐3p expression is down‐regulated in cSCC cell lines and miR‐342‐3p is down‐regulated in cSCC tissues compared to adjacent non‐tumor specimens. We showed that the SCARNA2 expression is negatively associated with miR‐342‐3p in cSCC. Moreover, we noted that SCARNA2 sponges miR‐342‐3p expression in cSCC cells. Overexpression of SCARNA2 suppressed the miR‐342‐3p expressed in SCC13 cells. We found that elevated expression of SCARNA2 promotes cell growth, cell cycle and invasion via regulating miR‐342‐3p expression in SCC13 cells. Conclusions: These data suggest that SCARNA2 acts in an oncogenic role and may be a potential target for cSCC. Abstract : SCARNA2 expression was overexpressed in cSCC. (A) SCARNA2 expression was higher in cSCC tissues compared to adjacent non‐tumor samples. (B) The expression level of SCARNA2 was up‐regulated in 16 patients (16/20, 80%) compared to adjacent non‐tumor tissues. (C) SCARNA2 expression was up‐regulated in cSCC cell lines (A431, Tca8113, HSC‐5 and SCC13) compared to HaCaT.